Autoantibodies Associated With Connective Tissue Diseases: What Meaning for Clinicians? - Didier, Kevin; Bolko, Loïs; Giusti, Delphine; Toquet, Segolene; Robbins, Ailsa; Antonicelli, Frank; Servettaz, Amelie (Frontiers in Immunology, 2018)
Connective tissue diseases such as systemic lupus erythematosus, systemic sclerosis, myositis, Sjögren’s syndrome and rheumatoid arthritis are systemic diseases which are often associated with a challenge in diagnosis. Autoantibodies can be detected in these diseases and help clinicians in their diagnosis. Actually, pathophysiology of these diseases is associated with the presence of antinuclear antibodies. In the last decades, many new antibodies were discovered but their implication in pathogenesis of connective tissue diseases remains unclear. Furthermore, the classification of these autoantibodies is nowadays misused, as their targets can be localized outside of the nuclear compartment. Interestingly, in most cases each antibody is associated with a specific phenotype in connective tissue diseases and therefore help in better defining either the disease subtypes or diseases activity and outcome. Because of recent progresses in their detection and in the comprehension of their pathogenesis implication in connective tissue diseases-associated antibodies, clinicians should pay attention to the presence of these different autoantibodies to improve patient’s management. In this review, we propose to focus on the different phenotypes and features associated with each auto-antibody used in clinical practice in those connective tissue diseases.